Comparison between pre-operative magnetic resonance imaging findings and surgical features in Dachshunds suffering from thoracolumbar intervertebral disc extrusion - Turner, P. (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2007.